2001
DOI: 10.1248/bpb.24.316
|View full text |Cite
|
Sign up to set email alerts
|

Anti-metastatic Effect of the Sialyl Lewis-X Analog GSC-150 on the Human Colon Carcinoma Derived Cell Line KM12-HX in the Mouse.

Abstract: We investigated the inhibitory effect of the sialyl Lewis-X (sLeX) analog, GSC-150, on hepatic metastasis of the human colon carcinoma derived cell line, KM12-HX, which highly expresses sLeX antigen on the cell surface. The number of cancer nodules found in BALB/c nude mouse liver 6 weeks after intrasplenic injection of KM12-HX cells was significantly reduced by co-administration of GSC-150. The amount of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 16 publications
(29 reference statements)
0
13
0
Order By: Relevance
“…Shirota and colleagues investigated the inhibitory effect of a sLe x analog, GSC-150 on hepatic metastasis of human colon carcinoma in nude mice. They found that liver metastases were significantly attenuated when cancer cells were co-administered with GSC-150 (Shirota et al, 2001). In addition to sLe x analogs, novel disaccharides have been generated which function as competitive substrate inhibitors for glycotransferases involved in the synthesis of sLe x .…”
Section: The Biology Of Selectin-mediated Hematogenous Metastasismentioning
confidence: 99%
“…Shirota and colleagues investigated the inhibitory effect of a sLe x analog, GSC-150 on hepatic metastasis of human colon carcinoma in nude mice. They found that liver metastases were significantly attenuated when cancer cells were co-administered with GSC-150 (Shirota et al, 2001). In addition to sLe x analogs, novel disaccharides have been generated which function as competitive substrate inhibitors for glycotransferases involved in the synthesis of sLe x .…”
Section: The Biology Of Selectin-mediated Hematogenous Metastasismentioning
confidence: 99%
“…Shirota and coworkers developed GSC-150, a sLe X analog, and showed suppression of inflammation and reduced liver metastasis when administered to mice (Shirota et al, 2001) (Figure 6). Ulbrich and coworkers described dibenzoic acid-based pan-selectin inhibitors that block rolling and E-selectin adhesion in an induced peritonitis model of acute inflammation in mice (Table 6) (Ulbrich et al, 2006).…”
Section: Applications For O-linked Glycan Inhibitorsmentioning
confidence: 99%
“…The glycosylation pattern of tumor cells is therefore the focus in the development not only of new tools for tumor diagnosis and monitoring but also in the design of new anticancer drugs [8]. Attempts have been made to mount an immune response against tumor oligosaccharides by carbohydrate vaccines [9] and also to inhibit adhesive processes, such as the interaction between oligosaccharides and lectins, by synthetic carbohydrate analogues [1013]. …”
Section: Introductionmentioning
confidence: 99%